SETTLEMENT OF THE INFLUENCE RETURN ON ASSETS, CURRENT RATIO, DEBT TO ASSETS RATIO ON COMPANY VALUE MODERATED BY FINANCIAL DISTRESS AND TOTAL ASSETS TURNOVER IN THE FOOD AND BEVERAGE SUB SECTOR LISTED ON THE SOUTHEAST ASIA STOCK EXCHANGE PERIOD 2012 – 2020 - Denny Kurnia; Ahmad Firdaus; Deni Sunaryo; Mia Karlina (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
This study aims to determine the effect of Return On Assets, Current Ratio, and Debt to Assets Ratio on company value, which is moderated by Financial Distress and Total Assets Turnover in the food and beverage sub -sector which is listed on the Southeast Asian Stock Exchange for the 2012-2020 period. The data collected is secondary data with the documentation method in the form of the company's annual report. The analytical tool used to test the hypothesis is SPSS 26. The population in this study are companies in the Food and Beverage subsector which are listed on the Southeast Asian Stock Exchange with a total population of 147 companies. The sampling method used in this study used a purposive sampling technique in order to obtain 12 companies with a sample of 108 samples. The analysis technique used is multiple linear regression analysis, moderating regression analysis (MRA), partial test, and simultaneous test. The results of the study partially concluded that Return On Assets had no partial effect on the Price Earning Ratio, the Current Ratio had a significant effect on the Price Earning Ratio, and the Debt to Assets Ratio had a significant effect on the Price Earning Ratio. The results of the study simultaneously show that Return On Assets, Current Ratio, and Debt to Assets Ratio have a significant effect on the Price Earning Ratio. In moderation Earning Per Share is able to moderate the relationship between Return On Assets and Current Ratio to Price Earning Ratio, Earning Per Share is not able to moderate the relationship between Debt to Assets Ratio to Price Earning Ratio, Moderating Total Assets Turnover is not able to moderate the relationship between Return On Assets and Current Ratio to Price Earning Ratio, Total Assets Turnover is able to moderate the relationship between Debt to Assets Ratio to Price Earning Ratio.